2011
DOI: 10.3109/1354750x.2011.573095
|View full text |Cite
|
Sign up to set email alerts
|

Expression of insulin-like growth factor-II, matrix metalloproteinases, and their tissue inhibitors as predictive markers in the peripheral blood of HCC patients

Abstract: These results highlight the importance of profiling the expression of IGF-II, MMP-9, and TIMP-1 in the peripheral blood as prognostic molecular biomarkers in HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
2
15
1
Order By: Relevance
“…Other studies have demonstrated a significant increase in IGF-2 mRNA expression in human cirrhotic liver, in liver cancers and in the peripheral blood of HCC, in human hepatoma cell lines, in comparison to that of normal adult liver (37)(38)(39)(40). This discrepancy may be attributed to the fact that in the present study we measured only the free IGF-2 levels in serum but not mRNA.…”
Section: Discussioncontrasting
confidence: 49%
“…Other studies have demonstrated a significant increase in IGF-2 mRNA expression in human cirrhotic liver, in liver cancers and in the peripheral blood of HCC, in human hepatoma cell lines, in comparison to that of normal adult liver (37)(38)(39)(40). This discrepancy may be attributed to the fact that in the present study we measured only the free IGF-2 levels in serum but not mRNA.…”
Section: Discussioncontrasting
confidence: 49%
“…Studies have (El Tayebi et al, 2011) discussed the importance of IGF-2 in HCC recurrence and prognosis, which has a high expression in liver cancer tissue. IGF-II was influenced and regulated by IGF binding protein-3, matrix metalloproteinases (MMP) and tissue inhibitor of metalloprotienase-1 (TIMP-1).…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin can combine with somatostatin receptor (SSTR) expressed by tumor cells and then inhibit promoting tumor growth hormone or cytokine's production and adjust tumor blood supply (Hasskarl et al, 2011;Jiang et al, 2011;Zhang et al, 2011;Laznicek et al, 2012;Niu et al, 2012). Insulin-like growth factor-2 (IGF-2) is an important angiogenic factor during the process which HCC induced neovascularization (El Tayebi et al, 2011;Rehem et al, 2011;Wachter et al, 2012 of HCC. At present we have not yet found the study of IGF-2 expression in serum and prognostic impact which brought by the treatment of octreotide peptide combined with TACE to liver cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IGF-Ⅱ was found to be overexpressed in HCC and to promote tumor cell migration, proliferation and extra-hepatic metastasis [5][6][7][8] . Moreover, our research group has shown IGF-Ⅱ to be overexpressed in peripheral blood monocytes of HCC patients, and this aberrant expression was directly correlated with elevated serum levels of alfa-fetoprotein and poor prognosis [9] . IGF-1R was reported to be upregulated in 59% of HCC tissues in which it was associated with poor prognosis and tumors exceeding the Milan criteria [10] .…”
Section: Introductionmentioning
confidence: 94%